Digitalisasi Pemasaran Syariah Program Pekarangan Pangan Bergizi di Desa Winong Kecamatan Kedungwaru Kabupaten Tulungagung - Lantip Susilowati; Sri Eka Astutiningsih; Binti Nur Asiyah; Nita Agustina Nurlaila Eka Erfiana; Lisa Yuni Lestari; M. Nanang Febrianto; Vina Marotus Salsabila; Mey Susanti (Pusat Riset dan Inovasi Nasional, 2025)
Limited access to marketing local products is one of the main challenges in efforts to increase halal food security. Sharia digital marketing technology can be used as a marketing platform to obtain market accessibility and strengthen the branding of a product. This study aims to analyze the strengthening of digitalization of sharia marketing in supporting the Nutritious Food Yard (P2B) program in Winong Village. The method used in this study is Asset Based Community Development (ABCD) which emphasizes the use of local potential as the basis for program development. The results of the service show that Winong Village has potential assets in the form of P2B physical assets and organic agricultural products, social assets of the Women Farmers Group (KWT), and digital assets that are starting to develop. The implementation of the sharia digital marketing training program has succeeded in creating greenheavenumkm.com website as a digital marketing forum for MSMEs. The evaluation of training based on the results of the pre-test and post-test showed a significant increase in public understanding of sharia-based digital marketing strategies. This program has a positive impact, expands the reach of local product marketing, and is an effective strategy in strengthening the digitalization of sharia marketing in the P2B Program in Winong Village.